The Future of Management Control is Fair A New Perspective on Beyond Budgeting as Promoter of Trust and Ethical Behavior - Schmitz, Sven Olaf.; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2020)
The design of Management Control Systems (MCS) in the context of financial institutions should be reconsidered with regards to their ability to improve organizational justice perceptions. Promoting organizational justice can help banks to build significantly more trust and influence employees$1 (Bbehaviors in the best interest of the organization. Especially the design of Beyond Budgeting as a MCS that emphasizes social control mechanisms and facilitates autonomous working appears to be a promising concept for the design of future MCS in the context of financial institutions. Contents The Impact of MCS on Organizational Justice and Respective Outcomes Interrelation between MCS Design, Organizational Justice, Trust and Employees$1 (BBehaviour Beyond Budgeting$1 (Bs Impact on Organizational Justice, Trust and Behaviour Implications for the Future Design of MCS in Financial Institutions Target Groups Scientists and students in the field of banking, controlling, strategy, management, business psychology and business ethics Bank managers of cooperative and saving banks, controller at financial institutions, sales managers at banks and in sustainable banking About the Author Dr. Sven Olaf Schmitz has more than ten years of banking experience with a focus on digital transformation. In his current position he supports banks in developing new digital propositions and identify new collaboration areas. Sven Olaf$1 (Bs research projects aim to explore the potentials of Beyond Budgeting for managing banks in the 21st century.s
The Impact of MCS on Organizational Justice and Respective Outcomes -- Interrelation between MCS Design, Organizational Justice, Trust and Employees$1 (BBehaviour -- Beyond Budgeting$1 (Bs Impact on Organizational Justice, Trust and Behaviour -- Implications for the Future Design of MCS in Financial Institutions.s
Keywords: Management; Industrial psychology; Business ethics; Management; Industrial and Organizational Psychology; Business Ethics